1981
DOI: 10.1073/pnas.78.11.7043
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of double-stranded RNA associated with cytoplasmic male sterility in Vicia faba

Abstract: The cytoplasmic male sterility (CMS) trait of at least one line of Viea faba plants is always associated with the presence of high molecular weight double-stranded RNA in the leaf tissue extracts. Subcellular fractions of leaf tissue from CMS and fertile maintainer plants were initially analyzed in an attempt to locate, identify, and characterize the genetic material involved with the sterility trait. This CMS-associated high molecular weight RNA was found only in the cytosol of the "447" male sterile line ofV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1

Year Published

1982
1982
1999
1999

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 20 publications
1
49
1
Order By: Relevance
“…The presence of dsRNA in infected but not healthy plants as well as the fact that the concentration of extractable dsRNA in infected plants is related specifically to the time of infection and incubation temperature indicates that a virus is responsible for the disease. There have been some reports of dsRNAs being isolated from healthy plants either as small heterogeneous molecules (Ikegami & Fraenkel-Conrat, 1979) or as large homogeneous molecules consistently associated with one particular cultivar (Grill & Garger, 1981;Dodds et al, 1984); however, in our work a single cultivar of banana was used throughout and homogeneous high molecular weight dsRNAs were never found in healthy plants. Gildow et al (1983) strains MAV, PAV and SEV.…”
Section: -6725contrasting
confidence: 51%
“…The presence of dsRNA in infected but not healthy plants as well as the fact that the concentration of extractable dsRNA in infected plants is related specifically to the time of infection and incubation temperature indicates that a virus is responsible for the disease. There have been some reports of dsRNAs being isolated from healthy plants either as small heterogeneous molecules (Ikegami & Fraenkel-Conrat, 1979) or as large homogeneous molecules consistently associated with one particular cultivar (Grill & Garger, 1981;Dodds et al, 1984); however, in our work a single cultivar of banana was used throughout and homogeneous high molecular weight dsRNAs were never found in healthy plants. Gildow et al (1983) strains MAV, PAV and SEV.…”
Section: -6725contrasting
confidence: 51%
“…Büttner and Nienhaus (1989a, b) reported on virus contamination of soils and water in forested areas. The authors demonstrated that about 30% of the soil-root sam- (Grill and Garger, 1981;Wakarchuk and Hamilton, 1985). However, dsRNA species obtained from oak tissue were much smaller than nonviral dsRNA which were observed by these authors.…”
Section: Introductionmentioning
confidence: 80%
“…Laver et al, 1991;Johns et al, 1992), multiple intragenic recombin,ltion events generating chimeric gene arrangements (e.g. Younig and Hanson, 1987;Levings, 1993), oftm producing polyc~istronic messages and, in one case, unumal viruslike particles (Grill and Garger, 1981). This diversity of mutations initially made it difficult to identify those features linking each system to a similar aberrant phenotype.…”
Section: Cytoplasmic Male Sterlllty and Male Sterile Mutantsmentioning
confidence: 99%